2014
DOI: 10.3390/molecules191221560
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Pharmacokinetic Study of Gentiopicroside, Geniposide, Baicalin, and Swertiamarin in Chinese Herbal Formulae after Oral Administration in Rats by LC-MS/MS

Abstract: A sensitive and efficient liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed for the simultaneous determination of gentiopicroside, geniposide, baicalin, and swertiamarin in rat plasma. To avoid the stress caused by restraint or anesthesia, a freely moving rat model was used to investigate the pharmacokinetics of herbal medicine after the administration of a traditional Chinese herbal prescription of Long-Dan-Xie-Gan-Tang (10 g/kg, p.o.). Analytes were separated by a C18 column with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The observed m / z transition of geniposide was m / z 406 (M + NH 4 ) + instead m / z 389 (M + H) + indicates an adduct as (M + NH 4 ) + due to the containing ammonium acetate in the mobile phase. The fragmentation pattern of target compounds in the study to determine the bioactive compounds in the pharmaceutical herbal product and the subsequent pharmacokinetic studies are compatible with previous reports for quantitative mass transitions of these analytes [ 26 , 32 , 33 ]. The optimization of the chromatographic condition to separate the analytes was conducted with respect to mobile phase composition, column and elution.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The observed m / z transition of geniposide was m / z 406 (M + NH 4 ) + instead m / z 389 (M + H) + indicates an adduct as (M + NH 4 ) + due to the containing ammonium acetate in the mobile phase. The fragmentation pattern of target compounds in the study to determine the bioactive compounds in the pharmaceutical herbal product and the subsequent pharmacokinetic studies are compatible with previous reports for quantitative mass transitions of these analytes [ 26 , 32 , 33 ]. The optimization of the chromatographic condition to separate the analytes was conducted with respect to mobile phase composition, column and elution.…”
Section: Resultssupporting
confidence: 86%
“…High-performance liquid chromatography (HPLC) coupled with tandem mass spectrometry (MS/MS) techniques has been used for the identification and quantitation of complex biological matrices, including a wide variety of manufactured and natural chemicals, due to its highly sensitive and selective detection. The current trend in pharmaceutical analysis using tandem mass spectrometry is not only a movement towards quality control by quantifying bioactive compounds levels in herbal medicines but also a movement towards applying developed methods for pharmacokinetic studies of medicinal herbs [ 26 , 27 , 28 ]. Multiple compositional medicinal herbs for treating chronic liver disease under clinical conditions should also be noted for their pharmacokinetic parameters for safe administration [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many iridoid glycosides from natural products have been shown significant anti-inflammatory efficacy [26,27], while the targets of these anti-inflammatory ingredients are still unclear. Among the iridoid glycosides, SW as a representative active compound can be detected in vivo [28]. Previous studies have demonstrated that SW has been used for treating serum hepatitis [29].…”
Section: Discussionmentioning
confidence: 99%
“…C max is the highest reached concentration of a drug after administration of one dose and before the administration of a second dose; T max represents the time taken for the drug to reach the maximum concentration (C max ); t ½ is the time for the drug to reach half of its initial concentration; and AUC (area under the curve) refers to the total drug concentration over time [108]. The low absorption and intensive metabolism of the compounds with low bioavailability necessitate a more in-depth exploration of their bioavailability in animal and human studies [109]. A great number of polyphenols such as (−)-epiafzelechin, avicularin and isorhamnetin-3- O -neohesperidoside (flavonol 3- O -glycosides) have been determined using several liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) methods [110,111,112].…”
Section: Carob’s Polyphenols and Bioavailabilitymentioning
confidence: 99%